PENGARUH KUALITAS PELAYANAN INTI DAN KUALITAS PELAYANAN PERIFERAL TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP MINAT WORD OF MOUTH (Studi Pada Bengkel Body Repair Tri Tunggal di Kota Semarang) - Rombe, Febry Ferial; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyze the impact of service quality core and peripheral service quality to customer satisfaction and its impact on the interests of Word of Mouth. This study used multiple linear regression analysis using SPSS. The population used is the body repair workshop customers â€œTri Tunggalâ€ Semarang City in January-December 2014. While the sample used as many as 100 people with the techniques of non-probability sample selection sampling using accidental sampling. The results showed that the core service quality and peripheral service quality affects customer satisfaction and customer satisfaction affects the interests of Word of Mouth. In model 1, the quality of core services provide the greatest influence on customer satisfaction by 0,470. In model 2, the quality of core services provide giving effect to the greatest interest of Word of Mouth by 0,436